SHIFT OF THE WORD MEANING IN "DEVONU LUGOTIT TURK" ON THE BASIS OF METONYMY (Scientific journal of the Fergana State University, 2023)
Metonymy, one of the means of transferred meaning, is analysed according to the work  «Devonu lugotit turk»  by Mahmud Koshghari.